The Effectiveness of the Problem-Based Learning (PBL) Model and the Discovery Learning (DL) Model in Terms of Students’ Mathematics Learning Outcomes - Karo, Putri Vanessya Paskaria Br; Ratnawati, Oktaviana Ainun; Mairing, Jackson Pasini; Pancarita, Pancarita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2025)
This study aims to compare the effectiveness of the Problem Based Learning (PBL) and Discovery Learning (DL) models based on the learning outcomes of 10th-grade students at SMA Negeri 5 Palangka Raya. The research uses a quantitative approach with an experimental post-test only design. The samples used in this study were the students from classes X-2 and X-3. The data collection technique employed was a post-test to measure the students' learning outcomes. The results of the study show that (1) the Problem Based Learning (PBL) model is effective in improving the mathematics learning outcomes of students in class X-2 SMA Negeri 5 Palangka Raya, with 56% of students achieving scores above average. (2) Based on the t-test, the p-value for the DL model was found to be less than 0.05, indicating that the DL model provides a significantly better improvement in learning outcomes compared to the PBL model. The average post-test score for the class using the DL model (90.9) was higher than that of the class using the PBL model (80.28), showing a significant difference in learning outcomes